Novel Cricket World Cup Mass Gatherings Surveillance for Event-Based Surveillance in the Caribbean Region - Keston Daniel; Mohamed Elsherbiny; Sastee Kissoondan; Lisa Indar (Journal of Epidemiology and Global Health)
Abstract Objective To proactively identify and respond to potential health threats during mass gathering (MG) events using the regional MG Surveillance Framework across host countries for the 2024 T20 Cricket World Cup. Designs/Methods This framework, using multiple data sources, including the MG Surveillance module, provided daily intelligence and threat analysis to host nations. Specifically, the module allowed on-the-field data entry and immediate analysis; its infrastructure featured an Alerting mechanism built upon thresholds customized for MG events. Alerts were generated once thresholds were passed, notifying the relevant stakeholders immediately. Results Thirty-one MG and Health Facility Sites were registered onto the system and surveillance teams across the host countries were able to digitally capture 146 cases (generating 17 syndromic cases; 14 acute gastroenteritis-related and 3 fever with respiratory symptoms). The system reported non-communicable health issues like accidents/injuries (33 cases) and heat-related illnesses (22 cases). Conclusion The MG surveillance module illustrated its ability to provide health care practitioners and decision-makers with real-time data, syndromic alerts and analytics. The early warning and response mechanism facilitated early identification, communication and response to disease threats emanating from these events, and consequently reduce the risk of outbreak events that can overwhelm the health systems in the Caribbean.